Swap x and y's positions
f(x) is another way of saying y, so basically tha initial function is y = 1-2x^3.
Change it up to x = 1-2y^3 and solve for y
X - 1 = - 2y^3
(X - 1)/-2 = y^3
So the cube root of ((x-1)/2) = y
Answer:
= 4374.
Step-by-step explanation:
it is important to understand the pattern hidden in such problem.Let’s give it a try 2, 6, 18, 54 and so on.It can be written as 2, 3*2, 9*2, 27*2 and so on.
This can be further written as2 (1, 3, 9, 27, and so on) as 2 is common in every term.Now if you see the chain 1,3,9, 27 and so….you will see a pattern hidden i.e. 3=1*3 ,9=1*3*3, 27=1*3*3*3 now 27 is the 4th term consist of three 3. So 8th term would consist of seven 3. 8th would be 8th term = 1*3*3*3*3*3*3*3 = 2187 Hence the 8th term for the series 2,6,18,54 would be= 2*2187 = 4374.
364.5 because 9 to the third power is 729. 729 divided by 2 is 364.5
Answer:
a part of a line that has one endpoint and extends indefinitely in one direction
Step-by-step explanation:
a ray has one endpoint, then has an arrow going indefinitely in one direction.
Answer:
61.9047619048
Step-by-step explanation:
325/5.25= 61.9047619048